2013
DOI: 10.7205/milmed-d-13-00178
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Nutrition Intake of U.S. Military Service Members in Garrison

Abstract: Sparse information exists on the nutrition intake of U.S. military service members in a garrison setting. The purpose of this study was to assess the eating habits of a small group of service members who had not deployed in the preceding 12 months. Nutrition intake was measured using an online food frequency questionnaire and anthropometric measurements taken. Correlations were used to assess relationships between total caloric intake and sex, age, weight, waist circumference, body mass index, rank, marital st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 34 publications
1
31
0
2
Order By: Relevance
“…Although no studies linking nutrition knowledge and food intake have been conducted in military personnel, numerous studies (19)(20)(21)(22)(23)(24)(25) have reported dietary intake in this population to be inconsistent with public health and/or military nutrition recommendations. Characteristics of studies reporting poor dietary intake in this population include excessive consumption of fat, particularly SFA, unbalanced eating patterns with increased serves of 'extras' or 'treat' foods and inadequate fruit, vegetable and whole-grain consumption.…”
mentioning
confidence: 99%
“…Although no studies linking nutrition knowledge and food intake have been conducted in military personnel, numerous studies (19)(20)(21)(22)(23)(24)(25) have reported dietary intake in this population to be inconsistent with public health and/or military nutrition recommendations. Characteristics of studies reporting poor dietary intake in this population include excessive consumption of fat, particularly SFA, unbalanced eating patterns with increased serves of 'extras' or 'treat' foods and inadequate fruit, vegetable and whole-grain consumption.…”
mentioning
confidence: 99%
“…Research to date has shown that the health, fitness and performance of military personnel is highly reliant on their nutritional status during training, and, therefore, their readiness to be deployed can be negatively affected by suboptimal nutrient intakes [2][3][4][5]. This is particularly relevant to service members in combat roles when on base preparing/training for field deployment [6]. To support their training, a focus on a healthy and optimal diet is essential for facilitating training adaptations, recovery, maintenance of health, and career progression within the military.…”
Section: Introductionmentioning
confidence: 99%
“…The dietary requirements of active military personnel vary according to their occupation and work environment due to the differing physical and mental workloads across the vast range of roles and environments in which military personnel operate [6,9,10]. Considering [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations